Efficacy of essential oil of Piper aduncum against nymphs and adults of Diaphorina citri - Volpe, Haroldo X. L.; Fazolin, Murilo; Garcia, Rafael B.; Magnani, Rodrigo F.; Barbosa, José Carlos [UNESP]; Miranda, Marcelo P. (Society of Chemical Industry., 2015)
Insecticide application is the main way to control Diaphorina citri. However, it causes environmental contamination, has a negative impact on beneficial organisms and leads to psyllid resistance. The essential oil of Piper aduncum has low toxicity towards the environment and contains dillapiol, which has proven to be effective against several crop pests. Here, we studied its efficacy against nymphs and adults of D. citri under laboratory conditions. Oils with three concentrations of dillapiol (69.3, 79.9 and 85.4%) at 0.5, 0.75 and 1.0% dilutions plus 0.025% adjuvant were tested. All treatments caused 90-100% mortality in nymphs. Topical treatments with oil containing 79.9 and 85.4% dillapiol at 0.75% and 1% dilutions were effective (mortality ≥80%) in adults. However, the essential oil showed no residual activity against adults (mortality ≤30%). Dillapiol-rich oil is a promising compound for D. citri control. © 2015 Society of Chemical Industry.
Keywords: Asian citrus psyllid; Hlb; Active ingredient rotation; Botanical insecticide; Integrated pest management